2007
DOI: 10.1007/s11065-007-9043-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Behavioral Effects of Antiepilepsy Drugs

Abstract: Antiepilepsy drugs work by decreasing neuronal irritability, which may also result in the non-desired side effect of decreased neuropsychological function. In addition to cognitive side effects, antiepilepsy drugs (AEDs) may be associated with behavioral effects which may range from irritability and hyperactivity to positive psychotropic effects on mood. There have been many new medications released since the 1990s, and although they tend to have more favorable side effect profiles compared to their older coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
136
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(142 citation statements)
references
References 120 publications
(123 reference statements)
2
136
1
3
Order By: Relevance
“…Prior studies have shown that AEDs in and of themselves affect cognition. 32,33 In the current study, valproic acid affected attention more than either lamotrigine or ethosuximide. This highlights the importance of considering both cognitive and seizure outcome when evaluating optimal initial therapy.…”
Section: Statistical Analysis Baseline Neurocognitive Test Results Amentioning
confidence: 51%
“…Prior studies have shown that AEDs in and of themselves affect cognition. 32,33 In the current study, valproic acid affected attention more than either lamotrigine or ethosuximide. This highlights the importance of considering both cognitive and seizure outcome when evaluating optimal initial therapy.…”
Section: Statistical Analysis Baseline Neurocognitive Test Results Amentioning
confidence: 51%
“…However, some AEDs are endowed with unfavourable safety profiles, such as hepatotoxicity, toxicity to central nervous system (CNS) and show complex drug/drug interactions (Johannessen Landmark and Patsalos, 2010;Loring et al, 2007;Pennell, 2008). In recent years, pharmaceutical companies have developed new AEDs with improved safety profiles than the previously available ones.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of patients with epilepsy and in healthy volunteers, the distinct cognitive side effects associated with TPM have been well-described and studied. 1 No prospective dose-ranging studies of TPM's effect on cognition, however, have been performed, making it difficult to determine specific dose-related risk to neuropsychological function. Further, group studies have not characterized individual risk, but rather have relied only on group comparisons.…”
mentioning
confidence: 99%